Emotional intelligence and learning outcomes: Study in physical education - Albertus Fenanlampir; Toho Cholik Mutohir (UIR Press, 2021)
The correlation between emotional intelligence and learning outcomes of elementary school students in physical education is still minimal. Therefore, a deeper exploration in this study is carried out to reveal it. This study aims to analyze the correlation between emotional intelligence and students' physical education learning outcomes in elementary schools. This correlational study aims to analyze the relationship between emotional intelligence and elementary school students' learning outcomes in physical education. The ANOVA correlation between emotional intelligence and physical education learning outcomes shows a significance value of 0.224, greater than alpha 0.05. It means that there is no correlation between emotional intelligence and students’ cognitive learning outcomes in physical education subjects. Factors that contribute to the absence of a relationship between emotional intelligence and learning outcomes include implementing online learning that is less than optimal because it is not supported by adequate facilities and learning participation by all students. The other factors are reduced or limited interaction between students and the learning environment, the economic burden that causes parents’ emotional problem that impacts children's emotions. The contribution of emotional intelligence to the achievement of learning outcomes, especially in physical education subjects, is as much as 2%, and other factors contribute as much as 98%.